SURGICAL TREATMENT AND RECONSTRUCTION FOR CENTRAL GIANT CELL GRANULOMA OF MANDIBLE - case report and literature review. - Elitsa G. Deliverska (Journal of IMAB, 2013)
Introduction: Central giant cell granuloma (CGCG) is a benign aggressive destructive osteolytic lesion of osteoclastic origin. The central giant cell granuloma is often found in the mandible, anterior to the first molars. It most commonly occurs in patients under the age of 30, with a clear female prevalencePurpose: To present a case of CGCG of the lower jaw in Department of Oral and maxillofacial surgery, University Hospital "St. Anna". Although en bloc resection provides the lowest recurrence rate, only a few single case reports describe the use of this technique followed by reconstruction with autogenous bone grafts.Material and methods: The medical history of a 28 years patient with a large central giant cell granuloma in the mandible. Biopsy specimen taken from the lesion showed CGCG followed by curettage with peripheral ostectomy with preservation of the continuity of the mandible.Result: At the 1-year clinical and radiological follow up there was no sign of recurrence. Conclusion: After complete healing of the graft, prosthetic rehabilitation with implants will be perfomed. This allows the best functional and aesthetic results.